2010
DOI: 10.1080/09593331003793828
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic parameters and inhibition response of ammonia‐ and nitrite‐oxidizing bacteria in membrane bioreactors and conventional activated sludge processes

Abstract: Ammonium and nitrite oxidizing biomasses (AOB and NOB) were investigated in parallel pilot plants: a membrane bioreactor (MBR) and a conventional activated sludge process (CASP) fed with domestic wastewater. The kinetics of AOB and NOB were monitored through titrimetric tests. The maximum specific growth rate of the AOB (micro(max,AOB)) was affected by the solids' retention time (SRT) maintained during the start up: by varying the start up SRT from 20 d to 8 d, micro(max,AOB) in the CASP varied from 0.45 d(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…On the other hand, the average specific nitrifying capacity in this study (1.5 ± 0.3 g N g −1 VSS d −1 at SRT = 8 d) was clearly higher than the one obtained by Jubany et al [7] (0.7 ± 0.2 g N g −1 VSS d −1 at SRT = 30 d). This result agrees with those studies reporting an increase of the specific nitrifying capacity with a decrease of the SRT [18][19][20]. However, the main data for the design of a full-scale system is the treatment capacity or volumetric TAN oxidation rate (in g N L −1 d −1 ), which is a combination of the biomass concentration (in g VSS L −1 ) and its specific nitrifying capacity (in g N g −1 VSS d −1 ).…”
Section: Long-term Controlled Operation At Low Srt To Achieve a High supporting
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the average specific nitrifying capacity in this study (1.5 ± 0.3 g N g −1 VSS d −1 at SRT = 8 d) was clearly higher than the one obtained by Jubany et al [7] (0.7 ± 0.2 g N g −1 VSS d −1 at SRT = 30 d). This result agrees with those studies reporting an increase of the specific nitrifying capacity with a decrease of the SRT [18][19][20]. However, the main data for the design of a full-scale system is the treatment capacity or volumetric TAN oxidation rate (in g N L −1 d −1 ), which is a combination of the biomass concentration (in g VSS L −1 ) and its specific nitrifying capacity (in g N g −1 VSS d −1 ).…”
Section: Long-term Controlled Operation At Low Srt To Achieve a High supporting
confidence: 95%
“…Email: juanantonio.baeza@uab.cat (HRT = SRT), as in the SHARON process [17]. Moreover, the lower the SRT, the higher are the specific nitrifying rates [18][19][20]. However, the activated sludge systems working at low SRT have a limited treatment capacity due to the low biomass concentration that can be achieved and it was reported that the SHARON process could be limited by this restriction [21].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The previous statement can be illustrated simply with the example of half-saturation indices in MBR systems. Some studies have claimed that MBR systems select for bacterial groups with low half-saturation indices (K-strategists) as compared to CAS due to the high solids retention times (and thus low substrate levels) commonly employed in these types of systems (Munz et al, 2010). Other studies have reported these lower half-saturation indices to be due to the fact that floc sizes are smaller in MBR systems than in CAS (Manser et al, 2005).…”
Section: Discussion On Different Biological Treatment Systems and Thementioning
confidence: 97%
“…The treatment of decentralized domestic wastewater urgently requires measures which not only can meet environmental criteria for downstream discharge but also can satisfy realistic conditions [3]. Conventional wastewater treatment technologies such as activated sludge treatment methods [4][5][6], etc. are complicated and require overwhelming investment in terms of construction, operation and maintenance [7,8].…”
Section: Introductionmentioning
confidence: 99%